2017
DOI: 10.1016/j.appet.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and test meal intake among women with bulimia nervosa

Abstract: Many patients with bulimia nervosa (BN) also meet criteria for a lifetime alcohol use disorder (AUD). In order to understand possible mechanisms contributing to the co-occurrence and perpetuation of these disorders, this study investigated the importance of impulsivity and test meal intake among patients with BN by comparing women with BN only (n = 18), BN and current/past AUDs (n = 13), and healthy controls (n = 12). All participants completed assessments of eating disorder symptoms, frequency of alcohol use,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
(65 reference statements)
1
16
0
4
Order By: Relevance
“…Recent evidence suggests that treatment success in BN, BED, and obesity might be impaired by general and, more importantly, food‐specific self‐regulatory deficits (e.g., Brockmeyer et al, ; Manasse et al, ; Sysko et al, ). A number of studies suggested that the recruitment of the prefrontal control circuitry is altered in these conditions, which might explain the diminished self‐regulatory abilities in several executive functions, such as impulsivity, set shifting, or inhibition (Lavagnino, Arnone, Cao, Soares, & Selvaraj, ; Steward, Menchón, Jiménez‐Murcia, Soriano‐Mas, & Fernández‐Aranda, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that treatment success in BN, BED, and obesity might be impaired by general and, more importantly, food‐specific self‐regulatory deficits (e.g., Brockmeyer et al, ; Manasse et al, ; Sysko et al, ). A number of studies suggested that the recruitment of the prefrontal control circuitry is altered in these conditions, which might explain the diminished self‐regulatory abilities in several executive functions, such as impulsivity, set shifting, or inhibition (Lavagnino, Arnone, Cao, Soares, & Selvaraj, ; Steward, Menchón, Jiménez‐Murcia, Soriano‐Mas, & Fernández‐Aranda, ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were 183 individuals who participated in one of six previously published (Foerde, Steinglass, Shohamy, & Walsh, ; Gianini et al, ; Mayer, Schebendach, Bodell, Shingleton, & Walsh, ; Steinglass et al, , ; Sysko et al, ) or two ongoing eating behavior studies at the Columbia Center for Eating Disorders at the New York State Psychiatric Institute (NYSPI): 81 women and two men with AN, 30 women with BN, and 69 female and one male HC. HC were individuals with no current or prior eating disorder and included normal weight non‐dieters, as well as those who endorsed dieting, and obese individuals, as well as individuals who had lost at least 30 lbs.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were 183 individuals who participated in one of six previously published (Foerde, Steinglass, Shohamy, & Walsh, 2015;Gianini et al, 2015;Mayer, Schebendach, Bodell, Shingleton, & Walsh, 2012;Steinglass et al, 2014Steinglass et al, , 2018Sysko et al, 2017) (Fairburn & Cooper, 1993) and/or Eating Disorders Assessment-5 (Sysko et al, 2015). The parent studies included the baseline assessment from two pilot interventional studies (Steinglass et al, 2014;Steinglass et al, 2018).…”
Section: Participantsmentioning
confidence: 99%
“…Clinical studies testing this hypothesis have not yet been reported in humans and will be needed to confirm this hypothesis. Alternatively, several studies have found that elevated rates of impulsivity and behavioral disinhibition contribute to binge-eating episodes in patients with BN and BED [2][3][4][5][6]. Psychopharmacologic studies support a role for fluoxetine and lisdexamfetamine in treating…”
Section: Introductionmentioning
confidence: 99%